Exploring Understanding of Peripheral Artery Disease among Patients at High-Risk in Saudi Arabia: Results from an Interview-Based Study - Sultan Alsheikh; Abdulmajeed Altoijry; Shirin Alokayli; Sarah Ibrahim Alkhalife; Shahad Jamal Alsahil; Hesham AlGhofili (Clinics and Practice, 2023)
Background: The level of awareness of peripheral artery disease (PAD) in Saudi Arabia, especially among populations at high risk, is not currently well known. Therefore, our objective was to assess the existing level of awareness among patients who are at high risk of PAD, as well as their comprehension of the disease. Method: An interview-based cross-sectional study included 1035 participants with risk factors for PAD and collected data on demographics and knowledge domains related to PAD. Results: The statistical analysis was performed using t-tests and ANOVA. Overall, participants exhibited poor knowledge, with a mean score of 5.7 out of 26. The highest scores were observed in the risk factor and preventive measure domains, with means of 1.8 out of 7 and 1.8 out of 6, respectively. The factors associated with higher knowledge scores included older age, male gender, higher education, healthcare profession, interviews in vascular settings, previous awareness of PAD, and prior cardio-cerebrovascular interventions. Conclusion: This study underscores the inadequate knowledge of PAD among high-risk individuals. Targeted educational initiatives are essential to bridge this knowledge gap, potentially reducing the burden of PAD-related complications and improving patient outcomes. Efforts should focus on raising awareness about PAD, particularly among high-risk populations.